THE INFLUENCE OF INTERACTIVE MULTIMEDIA BASED ON ARTICULATE STORYLINE ON STUDENTS' LEARNING MOTIVATION IN GRADE X ECONOMICS LESSONS AT SMA NEGERI 1 IV KOTO - Walida Abida Hasibuan; Rita Syofyan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
Low student learning achievement reflects the same degree of lack of motivation to learn. The incorporation of interactive multimedia, particularly those developed with Articulate Storyline, is one of the likely solutions running in tandem with the existing instructional requirements. The aims of this study are to find out the effectiveness of interactive multimedia using Articulate Storyline in enhancing students' learning motivation at SMA Negeri 1 IV Koto. This research was carried out on class X phase E and two groups as samples: the control group and experimental group, each having 32 students. Data were collected using observation forms and questionnaires for motivation. Descriptive statistical analysis were used in the study, including normality tests, homogeneity tests, and hypothesis testing. Based on the research, multimedia created with Articulate Storyline significantly enhances students' motivation in the learning process. Paired Sample t-tests gave a significance of 0.000, which is less than 0.05, suggesting that students who were learning through the interactive multimedia and their counterparts learning under the traditional educational process differed significantly in motivation to study. Therefore, this study concludes that interactive multimedia developed using Articulate Storyline is an effective learning technology to increase students' motivation towards learning economics at SMA Negeri 1 IV Koto